1998
DOI: 10.1017/s0266462300010540
|View full text |Cite
|
Sign up to set email alerts
|

The National Patient Library: Evidence-based Information for Consumers

Abstract: A National Patient Library, a public/private partnership, is proposed to identify and vet information for consumers. Library staff will help tailor general information to consumers' specific needs. The library includes an electronic network. The principal focus of the library's information is controversial and experimental procedures, pharmaceuticals, and medical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This is a broad and loosely defined concept encompassing shared decision-making, patient education (including initiatives to promote public understanding such as the National Patient Library [110] in the USA) and involvement of patients or consumer advocates in the process of policy and guideline development [111].…”
Section: Patient Participationmentioning
confidence: 99%
“…This is a broad and loosely defined concept encompassing shared decision-making, patient education (including initiatives to promote public understanding such as the National Patient Library [110] in the USA) and involvement of patients or consumer advocates in the process of policy and guideline development [111].…”
Section: Patient Participationmentioning
confidence: 99%
“…After publication of the ECRI Institute guide for patients considering combined high-dose chemotherapy and bone marrow transplantation to treat breast cancer, researchers concluded that the alternative treatments chosen by some women may have spared them considerable pain and lengthened their lives, while lowering the cost. [20][21][22][23] …”
Section: What a Library Would Deliver-and To Whommentioning
confidence: 99%
“…In the U.S., a public‐private partnership has proposed a National Patient Library of evidence‐based health information intended to identify and vet information for consumers (Lerner, 1998). Already in existence for many years is Medline Plus, a service of the National Library of Medicine, which provides health topics, drug information, dictionaries and directories, as well as other information (Medline Plus, 2000).…”
Section: Health Systems Professionals and Patientsmentioning
confidence: 99%